The Relationship between Solvency Ratios and Profitability Ratios: Analytical Study in Food Industrial Companies listed in Amman Bursa - Abdul Rahman, Abdul Aziz A. (International Journal of Economics and Financial Issues, 2017)
This study aims to examine the relationship between solvency ratios and profitability ratios. The study was conducted on the food industrial companies listed in Amman Bursa during the period of 2012-2014. The results revealed no relationship between the following solvency ratios (debt/asset ratio, debt/equity ratio, long-term debt/assets ratio, long-term debt/equity ratio, and interest coverage) and the following profitability ratios (gross profit margin and operating cash flow margin). The results show negative relationship between both ratios of solvency (debt/asset ratio, debt/equity ratio) and the following profitability ratios (operating profit margin, net profit margin and return on assets). There are no relationships between the remaining of the solvency ratios (long-term debt ratios/ assets, long-term debt ratios/equity, and interest coverage) and the following profitability ratios (operating profit margin, net profit margin, and return on assets). Keywords: Solvency Ratios, Profitability Ratios, Food Industrial Companies, Amman, Jordan JEL Classification: M4